Proceedings of the Eighteenth International Symposium on Software Testing and Analysis 2009
DOI: 10.1145/1572272.1572297
|View full text |Cite
|
Sign up to set email alerts
|

Time-aware test-case prioritization using integer linear programming

Abstract: Techniques for test-case prioritization re-order test cases to increase their rate of fault detection. When there is a fixed time budget that does not allow the execution of all the test cases, time-aware techniques for test-case prioritization may achieve a better rate of fault detection than traditional techniques for test-case prioritization. In this paper, we propose a novel approach to time-aware test-case prioritization using integer linear programming. To evaluate our approach, we performed experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 43 publications
0
95
0
1
Order By: Relevance
“…In addition, previous research has shown that it is often appropriate to use automatically mutated faults for regression-testing experimentation [22], [24], [25]. In fact, Andrews et al [24], [25] found that for software-testing experimentation mutated faults are [20], which provides an API for solving mixed integer linear programming problems and has been widely used in other studies [5], [9].…”
Section: Dependent Variables and Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous research has shown that it is often appropriate to use automatically mutated faults for regression-testing experimentation [22], [24], [25]. In fact, Andrews et al [24], [25] found that for software-testing experimentation mutated faults are [20], which provides an API for solving mixed integer linear programming problems and has been widely used in other studies [5], [9].…”
Section: Dependent Variables and Metricsmentioning
confidence: 99%
“…For example, an industrial collaborator of Rothermel et al [1] reported that running the entire test suite for one of their software products takes nearly seven weeks. Therefore, researchers have developed various techniques to reduce the cost of regression testing through test-suite reduction [2]- [4], test-case prioritization [1], [5], [6], and regression test selection [7]. Yoo and Harman [8] presented a detailed survey of regression testing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the aim of test case prioritization is to rank the test cases to reveal faults earlier in order to reduce the cost of testing. There are numerous test case prioritization methods proposed in the literature [2,3,4,5,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55].…”
Section: Related Workmentioning
confidence: 99%
“…As it is time-consuming to run the aggregated tests, many test selection and/or reduction techniques [5,21,65,71] have been proposed to reduce the number of tests used in regression testing. To optimize the cost spent on regression testing, test prioritization techniques [61,62,68] have been proposed to schedule the execution order of tests. Most research in test selection, reduction and prioritization investigates various coverage criteria, including statement coverage, function coverage [12], modified condition/decision coverage [44], and so on.…”
Section: Regression Testingmentioning
confidence: 99%